Motor pattern of the knee joint muscles during side-step cutting in European team handball. Influence on muscular co-ordination after an intervention study - Bencke, J.; Naesborg, H.; Simonsen, E. B.; Klausen, K. (Scandinavian Journal of Medicine & Science in Sports, 2000)
The incidence of anterior cruciate ligament (ACL) injuries is reported to be high in many popular team sports The most risky movement in European team handball is reported to be the side-step cutting manoeuvre. Well-rehabilitated ACL-deficient athletes have been shown to have increased co-contraction about the knee joint with this manoeuvre. The aim of this study was to examine the effect of a prophylactic training programme on the co-contraction of the knee joints of non-injured European team handball players The subjects performed 'match-like' cutting manoeuvres on a force platform. EMG-signals from the involved knee joint muscles and force platform signals were simultaneously stored on a personal computer. The data collected before and after a 12-week prophylactic training program were compared. The results demonstrated that rehabilitation exercises cannot increase co-contraction about the knee joint in healthy athletes during side-step cutting. This is contradictory to the reported effect on ACL-deficient athletes. Scand J Med Sci Sports 2000 Apr;10(2):68-77